Efektifitas Penerapan Aplikasi Pediactric Triage Metode Jumpstart terhadap Penanganan Awal Kegawatdaruratan pada Anak - Syamsidar, Syamsidar; Rahim, Rachmawati; Akbar K., Fredy (Mando Care Jurnal, 2023)
Accidents involving students must be handled quickly and appropriately so that the readiness of teachers and employees at school is needed. One of the initial treatment methods in emergency cases is the pediatric triage Jumpstart method. This study aims to determine the effectiveness of using the pediatric triage Jumpstart method application on emergency management readiness in students of SDN 023 Kampung Baru, Luyo District, Polewali Mandar Regency. A population of 28 people using the purposive sampling method of 25 people are teachers and employees who are active at SDN 023 Kampung Baru, the research method uses experimental design with a pre and posttest one group design approach. To measure research variables using questionnaire instruments and observation sheets. The results of the study using a marginal homogenity test to determine the effectiveness of using the pediatric triage application of the Jumpstart method on the initial treatment of emergencies in students obtained a p value of 0.001 < 0.05.